Design, synthesis and evaluation of substituted piperidine based KCNQ openers as novel antiepileptic agents. Issue 10 (1st June 2018) - Yang, Shaoning; Lu, Dingqiang; Ouyang, Pingkai
Graphical abstract: Highlights: A series of novel substituted piperidine derivatives as KCNQ openers for treatment of epilepsy were investigated. Some compounds were found to be potent KCNQ2 openers. Compound 11 also possessed favorable PK profiles in rat. Abstract: Epilepsy is a kind of disease with complicated pathogenesis. KCNQ (Kv7) is a voltage dependent potassium channel that is mostly associated with epilepsy and thus becomes an important target in the treatment of epilepsy. In this paper, a series of substituted piperidine derivatives targeting KCNQ were designed and synthesized by using scaffold hopping and active substructure hybridization. Compounds were evaluated by fluorescence-based thallium influx assay, Rb + flow assay and electrophysiological patch-clamp assay. Results showed that some compounds possessed more potent potassium channel opening activity than Retigabine. More significantly, compound 11 was found to have good pharmacokinetic profiles in vivo .